Spectral characterization of a new cyclobutane and thiazole substituted Schiff base ligand and its Co(II), Cu(II), Ni(II), and Zn(II) complexes - Yilmaz, I; Çukurovali, A (Taylor & Francis Inc, 2004)
A novel bidentate Schiff base ligand containing cyclobutane and 2,4-disubstituted thiazole rings, 4-(1-methyl-1-mesitylcyclobutane-3-yl)-2-(2-hydroxy-5-methoxy benzylidenehydrazino) thiazole (HL), and its mononuclear complexes with a 1: 2 metal: ligand ratio have been prepared with acetate salts of Co(II), Cu(II), Ni(II), and Zn(II) in ethanol. The authenticity of the ligands and their complexes has been established by microanalyses, Lambdam, IR, H-1 and C-13 NMR spectra, and by magnetic susceptibility measurements. The thermal properties of all complexes have been studied by TG and DSC techniques. All the complexes were found to be mononuclear.
Keywords: cyclobutane; thiazole; Schiff base; complexes